MENGGAGAS TA’ARUF DAN KHITBAH YANG BERKEADILAN: Tela’ah Kitab Mambaus Sa’adah Karya KH. Faqihuddin Abdul Qodir - Safitri, Nuri; Jaenuri (Usrotuna: Journal of Islamic Family Law, 2024)
Abstract Marriage is realized through a series of aspects known as ta'aruf and khitbah. The implementation of khitbah is very important as well as the implementation of aqad, except that the implementation of this khitbah is a precursor before the contract. The problem to be studied is how the concept of ta'aruf and khitbah in the book of Mamba'us Sa'adah. The research method in this writing is library research, by reading and collecting books that discuss the problems of ta'aruf and khitbah. The reason the author chooses from the thoughts of Kh. Faqih is the concept of khitbah which must be done fairly for both the male and female parties. Ta'aruf and khitbah are the initial foundation for starting a good marriage. The concept of ta'aruf and khitbah in the book of Mamba'us Sa'adah is as follows. 1) knowing the religion, 2) knowing each other, 3) knowing each other's temperament, 4) not starting with coercion and lies, 5) not proposing someone else's proposal. Thus, of course, the concept of justice in khitbah is very important to do. Abstrak Pernikahan terwujud dengan melalui beberapa rangkaian aspek yang dikenal dengan ta’aruf dan khitbah. Pelaksanaan khitbah menjadi sangat penting seperti halnya pelaksanaan aqad, hanya saja pelaksanaan khitbah ini menjadi pendahulu sebelum adanya akad. Adapun permasalahan yang akan dikaji adalah bagaimana konsep ta’aruf dan khitbah dalam kitab mamba’us sa’adah. Metode penelitian dalam penulisan ini adalah penelitian kepustakaan (library research), dengan cara membaca dan mengumpulkan buku-buku yang mebahas tentang permasalahan ta’aruf dan khitbah. Alasan penulis memilih dari pemikiran Kh. Faqih adalah konsep khitbah yang harus dilakukan secara adil baik bagi pihak laki-laki dan perempuan. Ta’aruf dan khitbah adalah pondasi awal untuk mengawali sebuah pernikahan yang baik. Adapun konsep ta’aruf dan khitbah dalam kitab mamba’us sa’adah adalah sebagai berikut. 1)mengetahui agamanya, 2) saling mengenal satu sama lain, 3) mengetahui perangai satu sama lain, 4) tidak memulai dengan paksaan dan kebohongan, 5) tidak meminang pinangan orang lain. Dengan demikian tentunya konsep keadilan dalam khitbah sangar penting untuk dilakukan.